Efektivitas Model Pembelajaran Connected Mathematics Project (CMP) terhadap Kemampuan Berpikir Kreatif Siswa Kelas X SMA Negeri 1 Wiradesa - Ulya, Viki Himatul; Utami, Rini (Circle: Jurnal Pendidikan Matematika, 2024)
The aim of this research is to explain the effectiveness of the CMP learning model on students' creative thinking abilities. This research is quantitative research with an experimental approach using a Posttest Only Control Group Design. The research subjects consisted of 2 classes at SMA Negeri 1 Wiradesa, namely class X3 as the experimental class and class X5 as the control class. The data collection method used is the test method. The research results showed that there was a difference in the average creative thinking ability between the experimental class and the control class. students' creative thinking abilities because they exceed the previously determined KKM value. Therefore, the CMP learning model is effective for students' creative thinking abilities